Anti-consumerism: Stick or carrot? - Iwan Bos; Giovanni Maccarrone; Marco Marini (Fondazione Eni Enrico Mattei (FEEM), 2024)
Anti-consumerism is a doctrine that aims to discourage excessive consumption because of its damaging effect on the environment. It can either focus on creating psychic costs for consumers (a 'stick') or psychic benefits for non-consumers (a 'carrot'). This paper examines the impact of these two approaches on competition and welfare. The competitive effect is comparable in both cases - anti-consumerism (weakly) reduces competitive pressure as well as prices, outputs and profits. In terms of consumer and social welfare, however, the carrot performs strictly better than the stick.
Keywords: D11; L13; Q50; Q58; 330; Anti-Consumerism; Stick and Carrot; Environmental Externalities